Construções com régua e compasso e algumas aplicações - Araújo, Emanuel Oliveira de (2016)
This paper presents basic constructions made with ruler and compass were developed by ancient civilizations in order to perform daily tasks and build monuments. For this,the procedures used were based on lines and circles with the intention of finding the appropriate measure for these achievements. We show in this paper the main buildings made with these instruments, such as polygons and some algebraic measures. We analyze these buildings simply and algebraic way to justify the veracity of its findings. Also we will understand the concept of constructible numbers and characteristics. We learn to identify a number may or may not be constructed with ruler and compass. With this, we can see with clarity the classic problems of geometry and the real reason there is no building solutions to these problems. The purpose of this work is to recall some of the development of geometry and show the student that some formulas and equations can be designed so that your solution is revealed.